(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Road traffic accident is a disaster that can happen due to negligence. The accident can cause both physical injuries and property losses. Road Transportation Act 1987 makes it an obligation for all vehicle owners to have policy insurance that covers them from any loss. However, there are still parties involved, apart from the insured, that is not eligible to any compensation. The issue is how the compensation was calculated based on the insurance policy and the law regulating road traffic accident in Malaysia. The article analyses the possibility of integrating the principle of diat into the framework of compensation based on the insurance as ’aqilah. The research is done based on the theoretical analysis. It is found that insurance company and the motor insurance policy are consistent with the philosophy of ’aqilah. In terms of quantum of damages, it is found that the value under diat is much higher that those covered both under the insurance/takaful policy and Compendium of Personal Injury Awards 2014. It is also suggested that an automobile fund is set up to assist the unprotected victims. Keywords, diat, insurance, compensation, damages, risk, protection